ALGEBRAIC PROPERTIES OF INTUITIONISTIC FUZZY SET OPERATORS - KUMAR. S, SANTHOSH (International Journal of Mathematical Archive, 2018)
In this paper, some results are proved for establishing the algebraic properties of intuitionistic operators with respect to intuitionistic fuzzy sets.